Isolation of two novel purple naphthoquinone pigments concomitant with the bioactive red bikaverin and derivates thereof produced by Fusarium oxysporum. (21st November 2018) - Lebeau, Juliana; Petit, Thomas; Clerc, Patricia; Dufossé, Laurent; Caro, Yanis
Abstract : Filamentous fungi have gained growing interest as sources of diverse pigmented secondary metabolites. Some specific polyketides from Ascomycetous species have demonstrated a wide range of industrial applications in food, cosmetic, textile, and in the design of pharmaceutical products. The formulation of recipes containing fungal polyketides has increased over recent years. Fusarium strains were proven useful to mankind in a variety of technologies. Nevertheless, there is still need of new isolates of Fusarium for use in emerging and already existing fields. In this article, we report the concomitant production of the bioactive red bikaverin along with two novel purple pigments by the phytopathogenic Fusarium oxysporum LCP531 strain isolated from soil. In literature, the production of purple pigment had only been described in cultures of Fusarium Fujikuroi, Fusarium verticillioides, and Fusarium graminearum . The production of these naphthoquinonic pigments, their distribution (either produced in mycelia or excreted in liquid medium) and their chemical profiles were investigated with respect to nutrient composition. The pigments were extracted by using a pressurized liquid extraction method, monitored by colorimetric analysis and characterized by HPLC‐DAD chromatography. To our knowledge, this is the first report of these two novel wild‐type purple naphtoquinones pigments along with bikaverin, where additionally, the culture conditions were put into perspective to optimize fermentation cultures and extraction process accordingly to the pigment/biomolecule desired. These colored naphthoquinones should be promising fungal functional compounds which could be expected to have a place of choice, along with other antibacterial, antifungal, antiviral, anticancer, and antineoplastic derivatives. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2738, 2019